2017
DOI: 10.1002/gps.4840
|View full text |Cite
|
Sign up to set email alerts
|

Empirically derived dimensional syndromes of self‐reported psychopathology: Cross‐cultural comparisons of Portuguese and US elders

Abstract: The results support the syndrome structure of the OASR for Portuguese elders, offering Portuguese clinicians and researchers a useful instrument for assessing a broad spectrum of psychopathology. The results also offer a core of empirically supported taxonomic constructs of later life psychopathology as a basis for advancing clinical practice, training, and cross-cultural research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…To overcome this limitation, the Achenbach questionnaires are instruments capable of evaluating the clinical, sociodemographic and psychosocial competencies of older people, and it has recently been reported that the empirical syndromes of the Older Adult Self-Report (OASR) questionnaire (Achenbach et al, 2004), are generalizable to 19 different societies in America, Europe and Asia (Ivanova et al, 2020). The existing correlations between the empirical syndromes measured by the questionnaire have a positive and high magnitude among them, the highest correlation being the irritability / disinhibition syndrome with thought problems (rxy = .90), thought problems with anxiety / depression (rxy = .86), and memory / cognition problems with functional impairment (rxy= .82) (Ivanova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, the Achenbach questionnaires are instruments capable of evaluating the clinical, sociodemographic and psychosocial competencies of older people, and it has recently been reported that the empirical syndromes of the Older Adult Self-Report (OASR) questionnaire (Achenbach et al, 2004), are generalizable to 19 different societies in America, Europe and Asia (Ivanova et al, 2020). The existing correlations between the empirical syndromes measured by the questionnaire have a positive and high magnitude among them, the highest correlation being the irritability / disinhibition syndrome with thought problems (rxy = .90), thought problems with anxiety / depression (rxy = .86), and memory / cognition problems with functional impairment (rxy= .82) (Ivanova et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Older Adult Behavior Checklist (OABCL) questionnaire (Achenbach et al, 2004), developed in parallel to the OASR, and which reports the mental health of the elderly by third parties, shows moderate-high associations with scales from other questionnaires that measure the neuropsychological status of the elderly and geriatric depression (Brigidi et al, 2010). Both questionnaires have shown adequate internal consistency in international studies, α = .89 for OASR (Ivanova et al, 2017) and α = .91 for OABCL (Achenbach et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Ivanova et al tested the fit of the seven‐syndrome OASR model to self‐ratings by 352 adults who were 60 to 102 years old in community and residential care settings in Porto, Portugal . The OASR model showed good fit, as indicated by the primary model fit index, the root mean square error of approximation (RMSEA), and acceptable fit, as indicated by secondary fit indices, the comparative fit index (CFI) and Tucker‐Lewis index (TLI) .…”
Section: Introductionmentioning
confidence: 99%
“…Extending the single‐society CFA study of the Portuguese OASR, the present study used a multisociety design to test the seven‐syndrome OASR model in 20 societies from Asia, North and South America, and Europe. We used translations of the same standardized assessment instrument in each society, which allowed us to avoid the methodological challenges of having to combine data from different instruments …”
Section: Introductionmentioning
confidence: 99%
“…Na avaliação dos problemas de saúde mental utilizou-se um inventário de autoavaliação para adultos (Achenbach & Rescorla, 2003;Ivanova et al, 2018) que, além de um índice global de psicopatologia, fornece pontuações em 8 escalas relativas a problemas mais específicos (v.g., Ansiedade/Depressão, Queixas somáticas). Algumas destas escalas podem ser agrupadas em 2 clusters -problemas de externalização e problemas de internalização.…”
Section: Instrumentosunclassified